2‐Hydroxy‐5‐nitropyridine and 5‐nitro‐2‐pyridone: Tautomerism, infrared, Raman, and NMR spectral interpretations, normal coordinate analysis, and DFT calculations. Issue 10 (10th July 2021) - Mohamed, Tarek A.; Shaaban, Ibrahim A.; Soliman, Usama A.; Zoghaib, Wajdi M.
Abstract: Raman (3700–50 cm −1 ) and infrared (IR) (4000–230 cm −1 ) spectra of 2‐hydroxy‐5‐nitropyridine (HNP; C5 H4 N2 O3 ) have been recorded in the solid phase in addition to 1 H, 13 C, and 15 N nuclear magnetic resonance (NMR) spectra of the sample in dimethyl sulfoxide‐ d 6 (DMSO‐ d 6 ). Initially, keto and enol tautomeric forms were proposed owing to proton transfer from the hydroxyl group to pyridine nitrogen atom. Quantum mechanical calculations based on density functional theory (DFT; B3LYP, ωB97XD, and mPW1PW91) were carried out using 6‐31G(d) and 6‐311++G(d, p) basis sets favoring keto ‐NPO, 5‐nitro‐2‐pyridone, tautomer by ~0.857–1.345 kcal/mol with minor enol ‐HNP in the gas phase. Moreover, 1 H, 13 C, and 15 N NMR chemical shifts were predicted using gauge‐invariant atomic orbital‐DFT calculation at 6‐311++G(d, p) basis set using integral equation formalism of the polarization continuum solvation model including solvent effects. The calculated chemical shifts and spin–spin coupling constants ( J HH ) for keto tautomer better resemble those experimentally observed rather than the enol form. The observed IR/Raman bands were assigned quantitatively to their normal modes based on the calculated vibrational frequencies, force constants in internal coordinates, normal coordinate analysis, and potential energy distributions. Finally, the nitro and hydroxyl barriers to internal rotations were predicted via a relaxed potential energy surface scan using B3LYP/6‐311++G(d, p) calculations. The results are reported herein and compared with similar molecules whenever appropriate. Abstract : keto – enol tautomerism was investigated for 2‐hydroxy‐5‐nitropyridine (HNP) using quantum mechanical calculations combined with spectral (Raman, infrared, and nuclear magnetic resonance ) analyses. The results totally favor the keto ‐NPO, 5‐nitro‐2‐pyridone, tautomer, which occurs as H‐bonded dimer in the solid state. Confident vibrational assignments were presented aided by normal coordinate analysis and potential energy distributions. The calculated/observed 13 C/ 15 N NMR chemical shifts verified the dominant keto ‐NPO in solution.